Sperm DNA Cryodamage in Domestic and Farm Animals: Detection Methods and Ways of DNA Integrity Improvement - Yurchuk, Taisiia; Pavlovich, Olena; Petrushko, Maryna (Problems of Cryobiology and Cryomedicine, 2023)
Here, we have presented the data describing the cryopreservation impact on DNA status of domestic and farm animal sperm, and described the main causes of DNA fragmentation and methods of its detection and DNA integrity preservation. The current methods to identify the DNA fragmentation rate have been shown to be quite efficient, but the choice for the optimal way is stipulated by animal species. The oxidative stress caused by an increased content of reactive oxygen species was recognized as the main mechanism in DNA cryodamage. To prevent this negative effect on germ genetic material, many protective media and rehabilitation solutions supplemented with antioxidants (non-enzymatic, enzymatic compounds, and nanoparticles) have been developed. Thus, determining the sperm DNA fragmentation rate and maintaining its integrity are the necessary steps to improve the efficiency of domestic animal gamete cryopreservation as a part of reproductive technologies. Probl Cryobiol Cryomed 2022; 32(3): 172–182